Blood damage in Left Ventricular Assist Devices: Pump thrombosis or system thrombosis?. Issue 3 (March 2019) - Selmi, Matteo; Chiu, Wei-Che; Chivukula, Venkat Keshav; Melisurgo, Giulio; Beckman, Jennifer Ann; Mahr, Claudius; Aliseda, Alberto; Votta, Emiliano; Redaelli, Alberto; Slepian, Marvin J; Bluestein, Danny; Pappalardo, Federico; et al.
Introduction: Despite significant technical advancements in the design and manufacture of Left Ventricular Assist Devices, post-implant thrombotic and thromboembolic complications continue to affect long-term outcomes. Previous efforts, aimed at optimizing pump design as a means of reducing supraphysiologic shear stresses generated within the pump and associated prothrombotic shear-mediated platelet injury, have only partially altered the device hemocompatibility. Methods: We examined hemodynamic mechanisms that synergize with hypershear within the pump to contribute to the thrombogenic potential of the overall Left Ventricular Assist Device system. Results: Numerical simulations of blood flow in differing regions of the Left Ventricular Assist Device system, that is the diseased native left ventricle, the pump inflow cannula, the impeller, the outflow graft and the anastomosed downstream aorta, reveal that prothrombotic hemodynamic conditions might occur at these specific sites. Furthermore, we show that beyond hypershear, additional hemodynamic abnormalities exist within the pump, which may elicit platelet activation, such as recirculation zones and stagnant platelet trajectories. We also provide evidences that particular Left Ventricular Assist Device implantation configurations and specific post-implant patient management strategies, such as those allowing aortic valve opening, are more hemodynamically favorable and reduce the thrombotic risk. Conclusion: We extend the perspective of pump thrombosis secondary to the supraphysiologic shear stress environment of the pump to one of Left Ventricular Assist Device system thrombosis, raising the importance of comprehensive characterization of the different prothrombotic risk factors of the total system as the target to achieve enhanced hemocompatibility and improved clinical outcomes.